KUALITAS PERMEN KERAS DENGAN SUBSTITUSI SARI JERUK KALAMANSI - Putri, Rensiana; Mustika, Sari; Farida, Anni; Yasih, Fitri (Ensiklopedia Research and Community Service Review, 2025)
Abstract: Hard candy is a non-crystalline candy that is cooked at high temperatures (140-1500C), which has a hard texture, shiny and clear appearance. Hard candy generally uses sucrose, glucose and water as raw materials, while other additional ingredients are dyes, synthetic flavors, and acidifiers. Storing hard candy at high temperatures also causes stickiness and graining problems. This study aims to analyze the quality of hard candy with calamansi orange juice substitution of 0%, 10%, 20%, 30%, and 40% with sensory tests including color, appearance, texture, aroma and taste. The type of research conducted is a pure experiment using a Completely Randomized Design (CRD) with five treatments and 3 repetitions. Data collection techniques are carried out by giving questionnaires to 50 untrained panelists. Tabulated data using the ANOVA Test and if there is a difference, it will be continued with the Duncan Test. The results of this study indicate that the substitution of calamansi orange juice gives significant and insignificant results on the quality of color, appearance, texture, sweetness, sourness, and aroma with a concentration of 40% so that it increases the best color concentration with a value of X4 (5.82) with a very yellow category, for the best aroma quality results are at X4 (5.07) with a typical orange aroma category, the best sour taste results are at X4 (4.43) with a fairly sour category, the best appearance quality results are at X4 (5.39) with a shiny category, the best texture quality sensory test results are at X4 (5.19) with a hard category, the best sweet taste sensory test results are at X0 (5.36) with a sweet category. While for the best taste test results are at the X3 value for the quality of appearance, texture and sweetness and at the X4 value for the quality of color, taste, and sourness.Keywords: Quality, Hard candy, Calamansi Orange Juice.